Emerging Research in Artificial Intelligence and Computational Intelligence International Conference, AICI 2012, Chengdu, China, October 26-28, 2012. Proceedings - Lei, Jingsheng; Wang, Fu Lee.; Deng, Hepu.; Miao, Duoqian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the International Conference on Artificial Intelligence and Computational Intelligence, AICI 2012, held in Chengdu, China, in October 2012. The 163 revised full papers presented were carefully reviewed and selected from 724 submissions. The papers are organized in topical sections on applications of artificial intelligence; applications of computational intelligence; data mining and knowledge discovering; evolution strategy; intelligent image processing; machine learning; neural networks; pattern recognition.
Applications of artificial intelligence -- Applications of computational intelligence -- Data mining and knowledge discovering -- Evolution strategy -- Intelligent image processing -- Machine learning -- Neural networks -- Pattern recognition.
Keywords: Computer science; Information theory; Data mining; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Theory of Computation; Data Mining and Knowledge Discovery; Image Processing and Computer Vision; Pattern Recognition